Implementation and Operational Research: A Time–Motion Analysis of HIV Transmission Prevention Counseling and Antiretroviral Adherence Messages in Western Kenya. (1st August 2015) - Were, Martin C.; Kessler, Jason; Shen, Changyu; Sidle, John; Macharia, Stephen; Lizcano, John; Siika, Abraham; Wools-Kaloustian, Kara; Kurth, Ann
Abstract : Background: Shortages of health workers and large number of HIV-infected persons in Africa mean that time to provide antiretroviral therapy (ART) adherence and other messages to patients is limited. Methods: Using time–motion methodology, we documented the intensity and nature of counseling delivered to patients. The study was conducted at a rural and an urban HIV clinic in western Kenya. We recorded all activities of 190 adult patients on ART during their return clinic visits to assess type, frequency, and duration of counseling messages. Results: Mean visit length for patients at the rural clinic was 44.5 (SD = 27.9) minutes and at urban clinic was 78.2 (SD = 42.1) minutes. Median time spent receiving any counseling during a visit was 4.07 minutes [interquartile range (IQR), 1.57–7.33] at rural and 3.99 (IQR, 2.87–6.25) minutes at urban, representing 11% and 8% of total mean visit time, respectively. Median time patients received ART adherence counseling was 1.29 (IQR, 0.77–2.83) minutes at rural and 1.76 (IQR, 1.23–2.83) minutes at urban ( P = 0.001 for difference). Patients received a median time of 0.18 (0–0.72) minutes at rural and 0.28 (IQR, 0–0.67) minutes at urban clinic of counseling regarding contraception and pregnancy. Most patients in the study did not receive any counseling regarding alcohol/substance use, emerging risks for ongoing HIV transmission. Conclusions: Although ART adherence was discussed with most patients, time was limited. Reproductive counseling was provided to only half of the patients, and "positive prevention" messaging was minimal. There are strategic opportunities to enhance counseling and information received by clients within HIV programs in resource-limited settings.